Development and economic trends in anticancer drugs licensed in the UK from 2015 to 2019 - Lythgoe,MP; Krell,J; Mahmoud,S; Mills,E; Vasudevan,A; Savage,P (Drug Discovery Today, 2021)
Analysis of new anticancer drugs licensed in the UK found that 44 new therapies were approved from 2015 to 2019. No other 5-year period has produced as many new therapies. Most new drugs are kinase inhibitors (KIs, N = 18) and monoclonal antibodies (mAbs, N = 16) with only one classical cytotoxic chemotherapy (CC) licensed. The average median treatment duration has risen by 55 days to 318 days (263 days in 2010–2014). Drug costs have escalated; an average treatment course now costs £62 343, compared to £35 383 in 2010–2014. New drugs are delivering significant clinical benefits with longer treatment durations. However, the financial burden is greater, heralding economic challenges for healthcare providers.